Tłumaczenie a vista w dydaktyce innych rodzajów translacji a wyniki ankiety ogólnopolskiej - Monika Nader-Cioczek (Linguistische Treffen in Wrocław, 2025)
This paper focuses on the findings of a 2018/2019 survey on sight translation in translator/interpreter training conducted at Polish universities. The questionnaire comprised of 26 questions about sight translation as an additional tool in translator/interpreter training was addressed to the academics from the Departments of Applied Linguistics and German Studies in Poland. The aim of the study was to determine possible applications of sight translation in teaching other types of translation and interpreting, as well as to identify competences required for an effective sight translation performance. Consequently, the data obtained were intended to facilitate the author’s further research on sight translation and its implementation in translator/interpreter training, as well as to contribute to the development of a model for sight translation teaching. Analysis and evaluation of questionnaire feedback provide evidence for popularity and usefulness of sight translation in teaching other types of translation and interpreting. Sight translation is used in the pre-translation/pre-interpreting phase as an introduction to a given topic or as a consolidation or a follow-up task to a particular translation/interpreting exercise. Furthermore, it is a valuable aid in the development of various skills and competences concerning reading, code-switching and speaking. The study proves that sight translation contributes to the development of skills required in target text production, i.e. creating an outline of the target text, speaking in public, creating texts of various types and on particular topics, maintaining coherence and cohesion in the target text as well as divided attention to multitask. Sight translation in translator/interpreter training can have a positive impact not only on the improvement of vocabulary and grammar in a given situational or communication context but also on the increase of cultural awareness in the target language.